Developing cirebonese culture based syllabus of English club in Kedawung vocational state high school - Desy Dellita; Susilawati Susilawati; Ikariya Sugesti (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
This study aimed at finding out the target needs and learning needs of English Club members and designing the appropriate sylllabus speaking based Cirebonese Culture of English club member in Kedawung Vocational State High School. This study focused on extracurricular of English Club which consist of 38 members. Research and development (R&D) was used as the design of the study. The steps of the study were conducting needs analysis including the target needs and learning needs, writing the first syllabus, expert judgment, and writing the final syllabus. Interview, observation, document analysis, needs analysis questionnaire, and expert judgment analysis were used as the instruments of the study. The result of analysis for general aspect analysis was 3.07 or very good. Which means that the syllabus design based Cirebonese culture was appropriate to the English club members’ needs. Keywords: Syllabus design; English Club; Cirebonese Culture